PENGARUH JUMLAH WAJIB PAJAK TERDAFTAR DAN PENERBITAN SURAT PAKSA TERHADAP PENERIMAAN PAJAK PENGHASILAN PADA KPP PRATAMA MALANG UTARA - Diyah Anisa; Nur Diana; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2021)
Taxes are mandatory contributions paid by the people to the state without direct contribution and will be used in the interests of the government and the general public (Mardiasmo: 2011). According to Law Number 6 of 1983 as last amended by Law Number 28 of 2007 concerning General Provisions and Tax Procedures, it is stated that